CCEA GCSE Mathematics Higher Practice Book for 2nd Edition. - Anne Connolly; Linda Liggett; Robin Liggett (London, UNKNOWN : Hodder Education Group, 2017)
Provide structured support and extra practice with hundreds of practice questions that focus on problem-solving, building the exam skills needed to succeed in the new GCSE specifications. - Enhance learning and build exam skills with extra practice designed to support the student books - Help develop students' skills and prepare them effectively for their exam with questions that cover all units of the new syllabus - Build problem-solving and mathematical reasoning skills with a range of practice questions.
39 Constructions and loci (M7)40 Compound measures (M3); 41 Transformations (M7, M8); 42 Questionnaires (M3); 43 Statistical diagrams (M3); 44 Statistical averages and spread (M3); 45 Cumulative frequency curves and box plots (M3); 46 Histograms and sampling (M4); 47 Probability (M7, M8).
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Print version record.
Added to collection customer.56279.3
Keywords: Mathematics -- Examinations -- Study guides; Electronic books